A Completely Randomized Design (CRD) for Tomato Plant Growth and Production on Different Planting Media - Dahliani, Lili; S, Shumaila; Darmayanti, Rani (Assyfa Journal Scientific Essay, 2023)
Tomatoes possess versatile properties, serving not only as a vegetable but also as a valuable resource in the pharmaceutical, cosmetic, and food processing sectors. The cultivation of tomato plants to attain optimal development and output is significantly influenced by environmental conditions. The objective of this study is to identify optimal planting substrates conducive to the growth and yield of tomato plants. The study employed a Completely Randomized Design (CRD) for its research methodology. The findings of the study indicated that the growth (specifically plant height and number of leaves) and production (including fruit weight and number of fruit) of tomato plants were influenced by the planting media. The treatment, including the combination of soil planting media and cow dung, yielded the most favorable results regarding growing media utilization.